Oral administration of glycyrrhizic acid with intramuscular injection of foot-and-mouth disease vaccine enhances the adaptive immune system - Shin, Seokwon; Kim, Hyeong Won; Ko, Mi-Kyeong; Park, So Hui; Park, Jong-Hyeon; Kim, Su-Mi; Lee, Min Ja (Frontiers in Microbiology, 2025)
BackgroundCommercial foot-and-mouth disease (FMD) vaccines have several drawbacks, including a short duration of the immune response after vaccination and local adverse reactions at the vaccination site. Therefore, we developed a new vaccination strategy that simultaneously improves the health status of the host and stimulates systemic immunity by combining the oral administration of glycyrrhizic acid (GA) and intramuscular injection of the FMD vaccine.MethodsWe evaluated the efficacy of the oral immune enhancer GA in conjunction with an intramuscular injection of the FMD vaccine. After vaccination, the experimental (mice) and target animals (pigs) were orally administered GA daily for 4 weeks and once a week for the next 4 weeks. Subsequently, we evaluated safety using various biochemical serum assays, the efficacy of inducing immune responses using serological assays, and the expression of genes related to systemic immunity induction.ResultsOral administration of GA in combination with an intramuscular injection of the FMD vaccine enhanced early, mid-term, and long-term immunity in experimental and target animals. We also confirmed that this co-administration increased the expression of secretory IgA (sIgA), an important indicator of mucosal immunity. Additionally, significant gene elevations in systemic immune markers along with T helper (Th) immune responses were observed.ConclusionThese findings suggest that combining the oral administration of GA with the intramuscular injection of an inactivated FMD vaccine can induce a potent and sustained immune response and stimulate the systemic immune system by promoting sIgA and cytokine gene expression. Our research can be used to enhance the efficacy of existing commercial vaccines as well as control other animal diseases by improving the host’s immune system.